Understanding the Implementation of Deep Learning Approach in English Teaching for SMA - Sujinem (MAN 1 Kota Kediri, 2025)
Deep learning focuses on active engagement, critical analysis, and meaningful application of knowledge, moving beyond surface-level memorization to cultivate a deeper understanding of the language. Integrating mindful, meaningful, and joyful learning enhances this approach: Mindful Learning fosters self-awareness and reflection, helping students develop a deeper connection to their learning process. Meaningful Learning links language skills to real-world applications, ensuring relevance and practicality. Joyful Learning increases motivation and confidence through engaging, interactive, and enjoyable activities. This article is to elaborate the implementation of a deep learning approach in senior high school English language teaching, drawing from Marton & Säljö’s (1976) framework. Advancements in AI, VR, and podcasts further support this approach by creating immersive and interactive learning experiences. This study highlights how a deep learning framework, when combined with these strategies, transforms English classrooms into dynamic and student-centered environments. Findings suggest that this holistic method enhances language proficiency, critical thinking, creativity, and cross-cultural communication, equipping students with essential skills for academic and professional success. By adopting these strategies, educators can move beyond traditional methods and foster an engaging, reflective, and impactful learning experience, inspiring students to develop a lifelong passion for mastering English.